A FIQH MUAMALAH REVIEW OF THE FINANCIAL MANAGEMENT OF THE CITY OF TUAL THROUGH REGIONAL SAVINGS (Case Study of the City of Tual's Regional Financial Management Agency) - Rahayaan, Ahmad (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2025)
This study explores the financial management of the City of Tual through regional savings, analyzed from a fiqh muamalah perspective. The focus is on the use of interest (riba)—defined in Islamic jurisprudence as profit gained from lending without real economic effort. Using a qualitative descriptive method, data were collected through interviews and observations at the Regional Financial and Asset Management Agency (BPKAD) of Tual. Findings show that the local government deposits idle funds in conventional banks and receives interest, which is then transferred to the Regional General Treasury Account (RKUD). This practice raises differing views in Islamic law: some scholars strictly forbid it (haram), others permit it under certain conditions (halal), while some regard it as doubtful (syubhat). From the perspective of maqashid shariah, the conditional permissibility of interest may align with the objectives of preserving life (hifz al-nafs) and wealth (hifz al-mal), especially in contexts where Islamic banking is not available. Nonetheless, this practice remains a point of ethical debate, emphasizing the need for Shariah-compliant financial alternatives in regional governance.